Analisis Komparatif tentang Iri Dengki dalam Tafsir Al-Mishbah dan Asy-Sya'rawi: Implikasi bagi Kehidupan Mukmin - Ulya, Nafilatul; Iqbal, Ipmawan Muhammad; Novitasari, Fajar (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This research aims to analyse and compare the interpretation of the verses about envy in Tafsir Al-Mishbah by M. Quraish Shihab and Tafsir Asy-Sya'rawi by Muhammad Mutawalli Ash-Sya'rawi. Using a comparative approach and literature research method, this study identifies similarities and differences in their understanding of the phenomenon of envy in the context of the Qur'an. The results show that both commentaries describe envy as a spiritual and social phenomenon that can disrupt the harmony of individuals and society. The implications of this interpretation are relevant in dealing with modern social challenges, including the negative influence of social media on social unity and spiritual well-being. This research not only contributes to the academic understanding of Qur'anic exegesis, but also provides insights for practical application in the daily lives of Muslims in maintaining a clean heart and living a meaningful life in accordance with Islamic values.